Spatial Analysis of Prostate Cancer Mortality and Its Relationship with Geographic Access to Health Services by Municipalities in Costa Rica, 2010 – 2016 - Murillo-González, Adrián (2024)
This paper aims to explain the distribution and behavior of prostate cancer mortality in Costa Rica based on geographic access to health services by municipalities. Methodologically, an ecological analysis is presented; its information source is the death database of the National Institute of Statistics and Census. To study the association between mortality and access to health services, the authors designed the Geographic Access Index to Health Services (GAIHS) and implemented Poisson regression models and the Geographically Weighted Regression (GWR). As a main result, an increasing trend of the disease in the population was found. The GAIHS shows that access to health services is not evenly distributed in the territory and is associated with PCa mortality. It is concluded that the northern zone of the country presents the greatest disadvantage in access to health services and that the territories with the worst GAIHS tend to increase mortality from PCa.